Development of Risk Prediction Model for Hepatocellular Carcinoma Progression of Indeterminate Nodules in Hepatitis B Virus‐Related Cirrhotic Liver. (March 2017) - Cho, Hyo Jung; Kim, Bohyun; Lee, Jung‐Dong; Kang, Dae Ryong; Kim, Jai Keun; Lee, Jei Hee; Shin, Sung Jae; Lee, Kee Myung; Yoo, Byung Moo; Lee, Kwang Jae; Kim, Soon Sun; Cheong, Jae Youn; et al.
Abstract : OBJECTIVES: This study was performed to evaluate long‐term outcome of indeterminate nodules detected on cirrhotic liver and to develop risk prediction model for hepatocellular carcinoma (HCC) progression of indeterminate nodules on hepatitis B virus (HBV)‐related cirrhotic liver. METHODS: Indeterminate nodules up to 2 cm with uncertain malignant potential detected on computed tomography of cirrhotic liver during HCC surveillance were analyzed retrospectively. HCC risk prediction model of indeterminate nodules in HBV‐related cirrhotic liver was deduced based on result of Cox regression analysis. RESULTS: A total of 494 indeterminate nodules were included. Independent risk factors of HCC progression were old age, arterial enhancement, large nodule size, low serum albumin level, high serum α‐fetoprotein (AFP) level, and prior HCC history in all included subjects. In subjects with chronic hepatitis B, old age (year; hazard ratio (HR)=1.06; P <0.001), arterial enhancement (HR=2.62; P =0.005), large nodule size (>1 cm; HR=7.34; P< 0.001), low serum albumin level (≤3.5 g/dl; HR=3.57; P =0.001), high serum AFP level (≥100 ng/ml; HR=6.04; P =0.006), prior HCC history (HR=4.24; P =0.001), and baseline hepatitis B e antigen positivity (HR=2.31; P =0.007) were associated with HCC progression. We developed a simple risk prediction model using these risk factors and identified patients at low, intermediate, and high risk for HCC; 5‐year cumulative incidences were 1%, 14.5%, and 63.1%, respectively. The developed risk score model showed good performance with area under the curve at 0.886 at 3 years, and 0.920 at 5 years in leave‐one‐out cross‐validation. CONCLUSIONS: We developed a useful and accurate risk score model for predicting HCC progression of indeterminate nodules detected on HBV‐related cirrhotic liver.